Feasibility study of suspended ion exchange for organic matter removal and disinfection by-product minimisation in UK lowland waters - Fernandez-Lozano, Javier; Jarvis, Peter; Dunn, Clair; Carra, Irene; Brookes, Adam (Institute of Water, 2021)
This investigation compared the performance of suspended ion exchange (SIX) and granular activated carbon (GAC) filtration for organic matter removal and reduction of trihalomethane (THM) and haloacetic acid (HAA) formation potential. SIX treatment resulted in increased organic matter removal (60%) when compared with GAC (45%). SIX treatment produced a stable treated water Dissolved Organic Carbon (DOC), while changes in brine concentration had no effect on the removal of organic disinfection by-product (DBP) precursors. Liquid chromatography organic carbon detection analysis (LC-OCD) showed that the differences in the organic matter removal by SIX in comparison to GAC were caused by the increased affinity of the SIX process towards the 1 kDa and 0.5-0.35 kDa organic matter size bands. These were the molecular weight fractions comprising most of the overall DOC. Organic matter removal was consistent with the minimisation of THM and HAA formation. THM formation was reduced by 50% and 65%, whereas HAA formation was lowered by 60% and 70% in comparison to the untreated water, after GAC and SIX treatment, respectively. A linear correlation between the Br:DOC ratio and the bromine substitution factor was found for THMs and HAAs, suggesting that the formation of Br-DBPs was not selective to the treatment but attributed to bulk organic matter removal and bromide content at source. The use of resin in chloride form increased the chloride to sulphate mass ratio and Larson Index suggesting a risk for increased corrosivity of SIX treated water in the distribution network.
Keywords: DBP precursors; corrosion; costs; HAAs; LC-OCD; SIX; THMs